O processo de tomada de decisão em agricultores de Boa Vista das Missões - RS - Dalcin, Dionéia (2010)
Before a context where the process of decision-making is considered complex and studies in this area focus on this complexity, as well as analysis of the individual, their bounded rationality and issues related to information for decision-making the research aims analyze the process of decision-making in agriculture, in terms of social, institutional, cultural, organizational and personal aspects. Thus, for its development was used a descriptive and quantitative survey, that is, was carried out a survey of data from 77 properties in the city of Boa Vista das Missões - Rio Grande do Sul. The analyses of data collected were due to quantitative methods, such as the description of the sample by frequency and the other data over the relationship between variables. With base on the results of the study, it is possible to verify a relationship between social, cultural, personal, institutional and organizational aspects and decision-making. These relationships are more present in aspects of basement (decisions based on information or experience, cost/benefit or intuition/impulse), nature (routine or innovative decisions) and response time (fast decisions and thoughtful and time consuming decisions) for the decisions. Thus, it is suggest that the studies will help to specify some relevant characteristics to the process of decision-making of the farmers, which so far in the literature were little explored.